2016
DOI: 10.1177/0308022616667959
|View full text |Cite
|
Sign up to set email alerts
|

The benefits and barriers to technology acquisition: Understanding the decision-making processes of older adults with age-related vision loss (ARVL)

Abstract: Introduction: While research has investigated the factors influencing acquisition and use of technologies/assistive devices by older adults, few studies have addressed the decision-making processes regarding technology adoption of older adults with age-related vision loss. Method: This critical ethnography engaged 10 older adults with age-related vision loss in narrative interviews, participant observation sessions, and semi-structured in-depth interviews to understand their decision-making processes related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 30 publications
(62 reference statements)
1
33
0
Order By: Relevance
“…For many older adults, the desire to remain independent stemmed from their wish to not be perceived as a burden to family, friends or society more generally. As such, technologies that enabled or prolonged independent performance in meaningful activities were met with great enthusiasm (Brownsell et al , 2000; Johnson et al , 2007; Horton, 2008; Hernández-Encuentra et al , 2009; Steggell et al , 2010; Van Hoof et al , 2011; Bowes and McColgan, 2013; Gramstad et al , 2014; Claes et al , 2015; Hill et al , 2015; Pino et al , 2015; McGrath and Astell, 2016; Berridge, 2017). For example: Now what could you ask for more than that and you're independent.…”
Section: Resultsmentioning
confidence: 99%
“…For many older adults, the desire to remain independent stemmed from their wish to not be perceived as a burden to family, friends or society more generally. As such, technologies that enabled or prolonged independent performance in meaningful activities were met with great enthusiasm (Brownsell et al , 2000; Johnson et al , 2007; Horton, 2008; Hernández-Encuentra et al , 2009; Steggell et al , 2010; Van Hoof et al , 2011; Bowes and McColgan, 2013; Gramstad et al , 2014; Claes et al , 2015; Hill et al , 2015; Pino et al , 2015; McGrath and Astell, 2016; Berridge, 2017). For example: Now what could you ask for more than that and you're independent.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, for many people with disabilities and their families, ease of setup and comfort of use were the most important factors in their decision about whether or not to use technology [10]. They were most likely to use technology if it was affordable and accessible, although younger people were more likely to be technology-tolerant and the barriers increased for older adults with disabilities [11].…”
Section: The Technology Challenge In Rehabilitationmentioning
confidence: 99%
“…Ironically, research has shown that the older population might be more willing to learn how to use technology, and in some instances, might be more prevalent users of technology than the younger generation [11]. The role of technology in the lives of the elderly is particularly important to acknowledge, as members of the older population are experiencing changes to their social circumstances with events such as retirement, death of a partner and perhaps physical limitations regarding their health.…”
Section: The Technology Challenge In Rehabilitationmentioning
confidence: 99%
See 2 more Smart Citations